2013
DOI: 10.1111/crj.12035
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and distribution of interstitial lung diseases in Turkey

Abstract: The overall incidence of ILD in Turkey was computed to be 25.8/100,000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 14 publications
3
46
1
7
Order By: Relevance
“…Overall, the crude prevalence of ILDs in our study is even greater than that reported by COULTAS (67-81 per 100000 in the US) [1] and the incidence is close to the highest estimates (25.8 per 100000 per year in Turkey) [4]. Two original findings are of particular interest.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Overall, the crude prevalence of ILDs in our study is even greater than that reported by COULTAS (67-81 per 100000 in the US) [1] and the incidence is close to the highest estimates (25.8 per 100000 per year in Turkey) [4]. Two original findings are of particular interest.…”
Section: Discussionsupporting
confidence: 64%
“…Interstitial lung diseases (ILDs) form a heterogeneous group of disorders that comprise more than 200 entities commonly encountered by general practitioners and physicians of various specialties [1][2][3][4]. ILDs are classically divided into four categories: (i) ILDs of known causes, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study that included 30 cases ≥65 years and 70 younger subjects, the ratio of female patients was found to be significantly higher in the older group (83.3% vs 50%) [5]. A multicenter Turkish study reported that sarcoidosis was the most common interstitial disease; 53% were female and 75% were ≤50 years old [13]. The most comprehensive epidemiological research in Turkey included 293 patients with sarcoidosis and was published in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that ILDs are more common in males, but CTD-ILDs are more common in females (22)(23)(24)(25)(26). Females are also prone to other autoimmune diseases as well (6,15,27,28).…”
Section: Discussionmentioning
confidence: 99%